Czy Europa potrzebuje zmiany doktryny ekonomicznej? - Balcerek, Marta (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
After World War II the Federal Republic of Germany was forced to decide about its economic system, choosing between liberalism and collectivism. However, neither of the two systems was suitable for German society, so German legal power sought an intermediate solution, a doctrine which would be located halfway on a scale between the two above-mentioned extremes. The resulting solution was the ordoliberal concept of the social market economy, a new economic doctrine implemented by Ludwig Erhard, Economics Minister, later elected Chancellor. The social market economy has since grown in importance, as it was adopted by The European Coal and Steel Community in 1951, and by The European Economic Community in 1957, finally becoming the leading economic doctrine in Europe.